The Influence of Price, Service Quality, and Promotion Against Decision Users Transportation Online (Grab) in Jakarta - Gregorius Widiyanto; Pujiarti Pujiarti; FX Pudjo Wibowo (Fakultas Bisnis, 2021)
The purpose of this research is to see price, service quality, and promotion partially (individually) or simultaneously (jointly) against the decisions of online transportation service users (Grab) in Jakarta. The research was conducted by spreading questionnaires, while the research method was using Simple Random Sampling. The independent variables in this study are price, service quality, and promotion, while the dependent variable in this study is the decision of online transportation service users (Grab) in Jakarta. The analysis method used is direct questionnaire analysis. Online transportation service users (Grab) in Jakarta are 300 online Grab service users in Jakarta. The analytical method used in this study uses the coefficient of determination analysis, multiple regression analysis of the F test and t test, using SPSS Version 25 which is based on data from online Grab transportation service users of 300 people. The t test shows that the price variable (X1) partially has a positive and significant effect (the t count of price is 2,452 > t table 1,65 and 0,015 < 0,05) on decisions of online transportation service users (Grab) in Jakarta. Service quality (X2) partially has a positive and significant effect (the t count of service quality is 9,286 > t table 1,65 and 0,000 < 0,05) on the decision of online transportation service users (Grab) in Jakarta. Promotion variable (X3) partially positive and significant effect (the t count of promotion is 5,431 > t table 1,65 and 0,000 < 0,05) on the decision of users of online transportation services (Grab) in Jakarta. The F test results obtained the F count is 72,020 with a significance value is 0,000 so that the value of F count > F table or 72,020 > 3,87 or the level of significance (sig) 0,000 < 0,05, it can be shown that the effect is simultaneously (together) between price, service quality, and Decision Users Transportation Online (Grab) in Jakarta and the R Square in this study means that variance in decision making can be taken by price, service quality, and promotion through a model of 42,2% and the remaining 57,8% comes from other variables excluding price, service quality, and promotion variables.